2011
DOI: 10.1017/s1742170511000111
|View full text |Cite
|
Sign up to set email alerts
|

Comparing conventional and organic olive groves in central Greece: plant and bird diversity and abundance

Abstract: The present study was conducted in Magnesia Prefecture, central Greece, during the period May-June 2007. It aimed at the comparison between conventional and certified organic olive groves with regard to olive and olive oil production, diversity of plants (herbaceous and woody) and diversity and abundance of avifauna. Correlations between variables within herbaceous plants (linear regression) and woody plants (Principal Component Analysis), and the role of integration time of olive groves to the organic system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 92 publications
1
36
0
3
Order By: Relevance
“…The above results for the herbaceous plant species richness are in line with the theory that claims that the correlations between herbaceous plant species richness and diversity are simple, positive and powerful [59]. Tuomisto and Ruokolainen (2005), Sulivan and Sulivan (2006), and Solomou and Sfougaris (2011) [60][61][62] found in their research a positive correlation between the species richness and the Shannon diversity index of herbaceous plants in orchards, olive groves and natural ecosystems.…”
Section: The Role Of Agricultural and Environmental Factors In The Yisupporting
confidence: 82%
“…The above results for the herbaceous plant species richness are in line with the theory that claims that the correlations between herbaceous plant species richness and diversity are simple, positive and powerful [59]. Tuomisto and Ruokolainen (2005), Sulivan and Sulivan (2006), and Solomou and Sfougaris (2011) [60][61][62] found in their research a positive correlation between the species richness and the Shannon diversity index of herbaceous plants in orchards, olive groves and natural ecosystems.…”
Section: The Role Of Agricultural and Environmental Factors In The Yisupporting
confidence: 82%
“…The families Poaceae, Asteraceae, and Fabaceae, which are among the richest families of the Mediterranean flora and the most common in olive orchards (e.g., Solomou & Sfougaris, 2011), were the predominant families in both mowing and tillage management systems. However, a clear effect of soil management on plant species diversity was observed almost from the first year of treatment application.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the four species that ranked higher IV in NVT (above 50), were previously reported in association with tillage (Verdú & Mas, 2004;Plaza et al, 2011). On the other hand, some of the more important species within NVM assemblage (Hordeum murinum L., Torilis nodosa (L.) Gaertner, Calendula arvensis L., Lamarckia aurea (L.) Moench, Campanula erinus L., and Poa annua L.) were reported in association with mowing (Mas et al, 2007) and other (Lolium rigidum Gaudin, Aegilops triuncialis L., Medicago spp., Galium tricornutum Dandy, and Hordeum murinum) with less intense tillage farming systems (Saavedra & Pastor, 1995;Plaza et al, 2011;Solomou & Sfougaris, 2011). Moreover, Galium tricornutum and Anthemis arvensis L., associated only with NVM, are arable species threatened in other European countries (Storkey et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nelson et al (2011) found that organic intercropping or other polycultural cropping systems can substantially improve the microbial and fungal health of multiple kinds of soil. Solomou and Sfougaris (2011) found through their studies of multiple organic farms in Greece that the use of multiple organic techniques such as intercropping and organic fertilizers can increase interspecies biodiversity of flora and fauna, which can have multiple benefits for ecosystem health such as resilience against disease; higher and faster rates of, and more stable methods for, pollination, and the potential for more nutritious produce. Another study conducted by Bilalis et al (2013) found that, in comparing conventional and organic maize and tomato farms in a semi-arid climate in Zimbabwe (a very similar climate to New Mexico), multiple alternative organic technologies reduced energy inputs by more than 25%.…”
Section: Discourses About Sustainabilitymentioning
confidence: 99%